Role of fluids in migmatites: CO2-H2O fluid inclusions in leucosomes from the Deep Freeze Range migmatites (Terra Nova Bay, Antarctica) - Giorgetti, G; Frezzotti, M; Palmeri, R; Burke, Eaj (Journal of Metamorphic Geology, 1996)
The metasedimentary sequence of the Deep Freeze Range (northern Victoria Land, Antarctica) experienced high-T/low-P metamorphism during the Cambro-Ordovician Ross orogeny. The reaction Bt + Sil + Qtz = Grt + Crd + Kfs + melt was responsible for the formation of migmatites. Peak conditions were c. 700-750 degrees C, c. 3.5-5 kbar and X(H20) c. 0.5). Distribution of fluid inclusions is controlled by host rock type: (1) CO2-H2O fluid inclusions occur only in graphite-free leucosomes; (2) CO2-CH4+/-H2O fluid inclusions are the most common type in leucosomes, and in graphite-bearing mesosomes and gneiss; and (3) CO2-N-2-CH4 fluid inclusions are observed only in the gneiss, and subordinately in mesosomes. CO2-H2O mixtures (41% CO2, 58% H2O, 1% NaCl mol.%) are interpreted as remnants of a synmig-matization fluid; their composition and density are compatible P-T-a(H2O) conditions of migmatization (c. 750 degrees C, c. 4 kbar, x(H2O) c. 0.5). CO2-H2O fluid in graphite-free leucosomes cannot originate via partial melting of graphite-bearing mesosomes in a closed system, this would have produced a mixed CO2-CH4 fluid in the leucosomes by a reaction such as Bt + Sil + Qtz + C +/- H2O = Grt + Crd + Kfs + L + CO2 + CH4. We conclude that an externally derived oxidizing CO2-H2O fluid was present in the middle crust and initiated anatexis. High-density CO2-rich fluid with traces of CH4 characterizes the retrograde evolution of these rocks at high temperatures and support isobaric cooling (P-T anticlockwise path). In unmigmatized gneiss, mixed CO2-N-2-CH4 fluid yields isochores compatible with peak metamorphic conditions (c. 700-750 degrees C, c. 4-4.5 kbar); they may represent a peak metamorphic fluid that pre-dated the migmatization